Methimazole-induced insulin autoimmune syndrome. (August 2016) - Jain, Nidhi; Savani, Malvi; Agarwal, Manyoo; Kadaria, Dipen
Background: Hypoglycemia in a critical care setting is often multifactorial with iatrogenic insulin use, sulfonylurea (SU) use, sepsis, adrenal insufficiency and insulinoma among the common causes. Insulin autoimmune syndrome (IAS) is a rare cause of hypoglycemia characterized by the presence of insulin-binding autoantibodies to the sulfhydryl group-containing agents. We report a case of methimazole-induced IAS managed in the intensive care unit. Case presentation: A 76-year-old woman with a history of primary hyperthyroidism was sent from a nursing home for unresponsiveness. Vital signs were significant for hypotension (74/46) and low blood sugars. Fluid resuscitations with normal saline and 50% dextrose stabilized the blood pressure (BP) to 135/75 and her blood glucose to 264. Due to respiratory distress and septic appearance, she required emergency intubation. Nursing home medications were noted for methimazole and absence of any insulin or SU use. Empiric antibiotic treatment was started and fluid resuscitation was continued while home medications were held. Her laboratory values were significant for elevated creatinine, lactic acid, serum cortisol, C-peptide, and insulin. Her cultures, SU screen and computerized tomography (CT) scan were negative for significant findings. On day 2, in addition to 10% dextrose, octreotide was initiated for recurrent hypoglycemia. Her blood glucose (BG) continued to drop throughout the day for which she required glucagon support and a D20 infusion. By day 4, the rate of infusion was titrated up and her BG continued to drop to <60 mg/dl despite D20, octreotide and tube feeds with concentrated calories (1.5 cal/ml). Due to her declining health, her family endorsed palliative care and she was extubated. After day 11, her hypoglycemic episodes resolved and she remained endogenously euglycemic. Conclusions: IAS is associated with methimazole use due to formation of autoantibodies to insulin after its interaction with Sulfhydryl (SH) group in methimazole. While IAS is a rare entity, it demands consideration in hypoglycemia in patients with autoimmune conditions.